Efektivitas Penggunaan Bahasa Indonesia dalam Presentasi dan Seminar Mahasiswa: Analisis Kesalahan Bahasa dan Dampaknya Terhadap Pemahaman Audiens - Alvian Maranalom Siregar; Queen Helen Br. Bukit; Tirza Grace Simamora; Lili Tansliova (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to explore the effectiveness of using Indonesian in student presentations and seminars. The method used in this research is the Quantitative Method using a Questionnaire. Questionnaires were distributed to 23 students who had attended seminars or student presentations. Research findings show that students still often make errors in grammar, spelling and word choice in talks and seminars. These grammatical errors can affect how well the audience understands the presentation or seminar material; Audiences who are distracted by grammatical errors will have a hard time following along. Therefore, so that students can use Indonesian in presentations and seminars well, they need to be guided and trained.